Innovation Strategy and Firm Performance in Jakarta: Evidence from Large–Medium Manufacturing and SME Ecosystems - Selamet Riyadi; Ahmad Rojikun; Achmad Tarmizi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study examines the role of innovation strategy in improving firm performance within Jakarta’s manufacturing ecosystem, encompassing large, medium-sized enterprises, and small and medium enterprises (SMEs). Using a quantitative explanatory approach, this research analyzes the causal relationships among leadership orientation, innovation strategy, investment level, and firm performance. Primary data were collected through structured questionnaires administered to owners and managers of manufacturing firms operating in DKI Jakarta. The data were analyzed using Structural Equation Modeling (SEM), preceded by Confirmatory Factor Analysis (CFA) to ensure measurement validity and reliability. The results indicate that leadership orientation has a significant positive effect on innovation strategy and investment level. Innovation strategy also significantly strengthens investment level, which in turn exerts a strong positive influence on firm performance. In addition, leadership orientation directly contributes to firm performance. These findings suggest that innovation-driven strategies, supported by effective leadership and sustained investment, are essential for enhancing productivity and competitiveness in Jakarta’s manufacturing sector. This study contributes empirical insights to strategic management literature and offers practical implications for managers and policymakers.